Effects of Human Chorionic Gonadotropin on the Testis of Adult Albino Rats: A Histological and Histochemical Study - Waleed Kasim; Maha Al-Sammak (University of Mosul, 2018)
Aims of the study: To evaluate the histopathological changes induced by human chorionic gonadotropin (hCG) on the adult testis and to correlate the changes with the levels of testosterone, LH and FSH, as well as to assess their reversibility. Methods: 80 adult male albino rats were divided into 4 groups; 3 treated and 1 control. The treated groups were received 10, 50 or 100 IU/kg BW of hCG, while the controls received normal saline. The doses were given twice weekly for 3 months via S.C. injections. Subsequently, on day 1, 30, 60 and 90 post therapy, blood samples and the testes were obtained for evaluation. Results: Low dose of hCG caused increase in number of germ and Sertoli cells. Contrary, higher doses decreased their population, and resulted in exfoliation of the germ cells. Furthermore, reduction in the thickness of the tubular basement membrane, congestion of the inter-tubular blood vessels and interstitial bleeding were observed in the higher dose groups. All the doses caused interstitial oedema, hyperplasia and hypertrophy of Leydig cells, as well as diminution in the collagen fibers. All these changes were reversible within 3 months. Conclusions: Only the low doses of hCG stimulate the spermatogenesis, whereas higher doses suppress sperm production.